The Relationship between Working Capital Management and Firm Performance of the SET50 Index in Thailand - Puriboriboon, Pratoomma (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The purpose of the study is to analyze the relationship of working capital management with firm performance of the SET50 Index in Thailand. This study takes working capital management as the independent variable, which is measured by cash conversion cycle and quick ratio. The dependent variables consist of other measures such as profitability (return on assets and return on equity ratios) and market value (price earnings and price-book value ratios). Sales growth and debt ratios were used as control variables. This study compiled 5 years of data for 25 companies from 2014-2018, and analyzed the data using multiple regression analytical methods. The results showed that the cash conversion cycle had a significant inverse relationship with profitability and market value. This shows that a shorter cash conversion cycle results in increased profitability and market value. Moreover, the study also found a significant positive relationship between firm quick ratios and profitability. However, there was no evidence of a statistical relationship between quick ratios and market value in the study. It showed that an increase in quick ratio performance resulted in an increase in profitability.